2020
DOI: 10.1080/21556660.2020.1838769
|View full text |Cite
|
Sign up to set email alerts
|

Use of oral rivaroxaban in cerebral venous thrombosis

Abstract: Background Cerebral venous thrombosis (CVT) is an uncommon cause of stroke in humans and the mainstay of treatment is anticoagulation unless contraindicated. Non-vitamin K oral anticoagulants have not been duly evaluated in randomized controlled trials in CVT. Objective To compare the efficacy and safety of oral rivaroxaban with vitamin K anticoagulant (warfarin) in preventing recurrent venous thromboembolism (VTE) in patients with CVT. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(62 citation statements)
references
References 29 publications
1
59
0
2
Order By: Relevance
“…The included studies were published from 2014 to 2021, consisting of two randomized controlled trials, 7,8 four prospective studies, [10][11][12][13] and eleven retrospective studies [14][15][16][17][18][19][20][21][22][23][24] . Four studies were from the USA, 17,20,23,24 three from Pakistan, 10,11,18 two from Germany, 16,19 and one study was from Iran, 15 Poland, 12 Portugal, 22 France, 21 and Italy 14 respectively. There were three multicenter studies conducted at different countries.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…The included studies were published from 2014 to 2021, consisting of two randomized controlled trials, 7,8 four prospective studies, [10][11][12][13] and eleven retrospective studies [14][15][16][17][18][19][20][21][22][23][24] . Four studies were from the USA, 17,20,23,24 three from Pakistan, 10,11,18 two from Germany, 16,19 and one study was from Iran, 15 Poland, 12 Portugal, 22 France, 21 and Italy 14 respectively. There were three multicenter studies conducted at different countries.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…et al found no difference in terms of efficacy between rivaroxaban and warfarin to cause recanalization following cerebral venous sinus thrombosis. 22 Limitation: No doubt this is a medium sized study, the result cannot be generalized to such patients at large in clinical practice. Further research with bigger sample size of such patients with more prolonged follow-up is required in this regard.…”
Section: Discussionmentioning
confidence: 95%
“…Maqsood et al studied the same in 45 patients with 21 in Rivaroxaban and 24 in the warfarin group. 17 They documented recanalization in 86% of cases of the Rivaroxaban group and 83% warfarin group at 6 months and 100% at 12 months. NIHSS (National Institute of Health Stroke Scale) score of 0 was obtained in 95% of Rivaroxaban group at follow up on 3 rd to 12 th month.…”
Section: Discussionmentioning
confidence: 96%